Enteral nutrition during bone marrow transplantation in patients with pediatric cancer: a prospective cohort study - Garófolo, Adriana (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Cancer patients undergoing bone marrow transplantation (BMT) often require nutritional therapy due to treatment toxicities. The aim here was to evaluate the use of tube feeding and its applicability, indications, contraindications and complications in these patients. DESIGN AND SETTING: Prospective observational study conducted at a public university in São Paulo between January 2002 and August 2007. METHODS: The patients were followed up daily in the BMT unit by a research dietitian. Tube feeding was indicated when oral supplementation proved to be insufficient, when the patient had severe malnutrition or there was an impediment to use of oral feeding. It was contraindicated in the presence of gastrointestinal toxicity of grade 3 and 4 or other conditions that implied a risk or hindered its use or placement. Complications of tube feeding were divided into minor and major, according to whether they had lifethreatening implications. RESULTS: Forty-two (47.2%) patients had indications for tube feeding: the main reasons were transplantation inadequate food and supplement intake, insufficient intake with malnutrition or weight loss, severe malnutrition or need for oral fasting. Thirty-one (73.8%) received tube feeding: 11 autologous and 20 allogenic patients (P = 0.04). The main contraindications were severe gastrointestinal toxicities and sinusitis. Minor complications from tube feeding were more prevalent in patients with allogenic BMT, but no major complications were observed. CONCLUSION: Enteral nutrition is a feasible procedure in patients undergoing BMT and should be encouraged. The main difficulty in BMT patients, in relation to tube feeding, is gastrointestinal toxicities.